Lanthanide luminescence to mimic molecular logic and computing through physical inputs - Rodríguez, Miguel Andres Hernnadez (2020)
The remarkable advances in molecular logic reported in the last decade demonstrate the potential of luminescent molecules for logical operations, a paradigm-changing concerning silicon-based electronics. Trivalent lanthanide (Ln3+) ions, with their characteristic narrow line emissions, long-lived excited states, and photostability under illumination, may improve the state-of-the-art molecular logical devices. Here, the use of monolithic silicon-based structures incorporating Ln3+ complexes for performing logical functions is reported. Elementary logic gates (AND, INH, and DEMUX), sequential logic (KEYPAD LOCK), and arithmetic operations (HALF ADDER and HALF SUBTRACTOR) exhibiting a switching ratio >60% are demonstrated for the first time using nonwet conditions. Additionally, this is the first report showing sequential logic and arithmetic operations combining molecular Ln3+ complexes and physical inputs. Contrary to chemical inputs, physical inputs may enable the future concatenation of distinct logical functions and reuse of the logical devices, a clear step forward toward input–output homogeneity that is precluding the integration of nowadays molecular logic devices.